MALE GAZE DALAM SASTRA FEMINIS: STUDI ATAS KARYA ABIDAH EL KHALIEQY DAN RATIH KUMALA - Febrianto, Anggit; Udasmoro, Wening (Widyaparwa, 2023)
Since the fall of Suharto in May 1998, women's involvement in literature has increased rapidly, causing a rush of feminist themes and content in literary works in this period. However, the literary works of women writers, even female feminists, are still unable to escape the tendency to objectify women. This study will show how women are positioned as objects of the voyeuristic scopophilia and fetishistic scopophilia of men in the Abidah El Khalieqy’s Perempuan Berkalung Sorban and Geni Jora and Ratih Kumala’s Tabula Rasa and Gadis Kretek. This study is descriptive qualitative. Data collection techniques were carried out using the literature study method, namely by reading carefully and thoroughly the four material object novels. Collected data will be analyzed using Male Gaze Theory by Laura Mulvey. The results of this study show that in the four novels, women consistently manifest as objects of the voyeuristic scopophilia and fetishistic scopophilia of men. This finding can be seen in the voyeuristic relationship between Samsudin-Annisa in Perempuan Berkalung Sorban, Zakky-Lola in Geni Jora, Idroes-Roemaisa in Gadis Kretek; as well as in the Galih-Krasnaya fetishistic relationship in Tabula Rasa. As voyeuristic objects, women bodies are degraded as appropriate territory to be conquered by men; while as a fetishistic object, women are constructed as a "perfect product" that functions to satisfy men's visual desires. Sejak kejatuhan Soeharto pada Mei 1998, keterlibatan perempuan di ranah sastra meningkat dengan pesat sehingga menyebabkan derasnya tema dan muatan feminisme dalam karya sastra pada pe-riode ini. Akan tetapi karya sastra dari penulis perempuan, bahkan dari feminis perempuan sekalipun, masih belum mampu keluar dari kecenderungan untuk mengobjektifikasi perempuan. Penelitian ini akan menunjukkan bagaimana perempuan didudukkan sebagai objek voyeuristic scopophilia dan fetishistic scopophilia laki-laki di dalam novel Perempuan Berkalung Sorban dan Geni Jora karya Abidah El Khalieqy serta Tabula Rasa dan Gadis Kretek karya Ratih Kumala. Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data dilakukan dengan metode studi pustaka, yaitu dengan pembacaan yang cermat dan menyeluruh terhadap empat novel objek material. Data yang sudah terkumpul kemudian akan dianalisis menggunakan Teori Male Gaze Laura Mulvey. Hasil dari penelitian ini menunjukkan bahwa dalam keempat novel objek material, pe-rempuan secara konsisten diposisikan sebagai objek voyeuristic scopophilia dan fetishistic scopophilia laki-laki. Temuan ini dapat dilihat dalam relasi voyeuristic Samsudin-Annisa di Perempuan Berkalung Sorban, Zakky-Lola di Geni Jora, Idroes-Roemaisa di Gadis Kretek; serta dalam relasi fetishistic Galih-Krasnaya di Tabula Rasa. Sebagai objek voyeuristic, tubuh perempuan didegradasi menjadi sebuah teritori yang pantas ditaklukkan laki-laki; sementara sebagai objek fetishistic, perempuan dikonstruksi sebagai sebuah “produk sempurna” yang berfungsi memuaskan hasrat visual laki-laki.